Solutions to Infection Prevention and Control challenges in developing countries, do they exist? - Sparke, Vanessa Leonie; Diau, Jason; MacLaren, David; West, Caryn (International Journal of Infection Control, 2019)
Implementing sustainable infection prevention and control (IP&C) programs in developing countries is challenging. Many developing countries experience high burdens of disease and political instability. In addition, they are affected by geographical and climatic challenges, and have unique social, cultural and spiritual beliefs, all of which contribute to a higher prevalence of healthcare associated infections. The aim of this integrative review is to identify existing solutions to the challenges faced by developing countries when implementing IP&C programs. An extensive literature review was conducted to explore improvements in infection control in rural hospitals in developing countries. Three electronic databases were searched for relevant articles written between 1980 and 2018, published in peer reviewed English language journals, and relating to hospitals, not community settings. The findings indicate that developing countries continue to face many challenges in implementing IP&C programs. Limited success has been described with some IP&C program components but it is clear that little original research on the topic exists. Notably scarce are studies on the influences that culture, religious and spiritual beliefs have on IP&C program implementation. This review highlights opportunities for further research into healthcare workers perceptions of disease causation and infection transmission, and the role this plays in the effective implementation of an IP&C program. By exploring these opportunities appropriate and culturally sensitive solutions may be identified, which can assist with the design and implementation of culturally relevant IP&C programs in these settings.